DIFERENTIAL DIAGNOSE САRDIOMEGALIE - Нестерак, Р. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
This work analysis literature results of reasons cardiomegalie. Differentiale diagnose with most distribution diseases, which doing to start cardiomegalie.